Indigenous counseling in the Visayas an exploratory study - Po, Fernando Tan (Education quarterly.)
This study is an attempt to identify the indigenous counseling techniques and strategies and the value system of the clients in the three rural communities: Bagonbon, Buluangan and Quezon. The "lingua franca" in these three rural communities is Cebuano. it is hoped that the knowledge gained from this study will greatly contribute to e better understanding of the Cebuanos, both as individual and as a social group.